Analisis Kemampuan Pemecahan Masalah Matematika Ditinjau dari Tingkat Self-Confidance Peserta Didik Kelas VIII - Rani Rizka Ramdani; Nyoman Sridana; Baidowi Baidowi; Laila Hayati (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This study aims to describe mathematical problem-solving ability based on the level of self-confidence. This type of research is a qualitative descriptive study with a quantitative approach. The data collection technique in this research is to provide test (10 multiple choice questions and 2 description questions), questionnaires, and interviews. The results showed that students with high level of self-confidence with high mathematical problem-solving abilities were able to achieve 3 out of 4 indicators of assessing problem solving abilities well, namely indicators of understanding problems, devising a plan, and carrying out the plans. Students with high level of self-confidence with moderate math problem solving abilities are able to achieve 1 of 4 indicators well, namely carrying out the plans, achieve 2 of the 4 indicators quite well, namely indicators of understanding problems and devising a plan, and less able to achieve 1 of 4 indicators namely looking back indicators. Students with high level of self-confidence with low math problem solving abilities are able to achieve 1 of 4 indicators well, namely indicators of understanding the problem. However, it does not reach 3 indicators, namely devising plans, is carrying out the plan and looking back.